A comprehensive comparison of fecal microbiota in three ecological bird groups of raptors, waders, and waterfowl - Zhao, Caiquan; Liu, Li; Gao, Li; Bai, Lige (Frontiers in Microbiology, 2022)
Gut microbiota plays a vital role in maintaining the health and immunity of wild birds. However, little is known about the comparison of the fecal microbiota between different ecological groups of wild birds, particularly in the Yellow River National Wetland in Baotou, China, an important transit point for birds migrating all over the East Asia-Australian and Central Asian flyways. Here, we characterized the fecal microbiota and microbial potential function in 8 bird species from raptors, waders and waterfowl using 16S rRNA gene amplicon sequencing to reveal the microbiota difference and microbiota interaction pattern. Results indicated there was no significant difference in α-diversity but a significant difference in β-diversity between three groups of birds. The fecal bacterial microbiota was dominated by Firmicutes, Proteobacteria, Actinobacteria and Bacteroidetes in all groups of birds. Furthermore, we identified 5 bacterial genera that were significantly higher in raptors, 5 genera were significantly higher in waders, and 2 genera were more abundant in waterfowl. Bacterial co-occurrence network results revealed 15 and 26 key genera in raptors and waterfowl, respectively. Meanwhile, the microbial network in waterfowl exhibited a stronger synergistic effect than that of in raptors. PICRUSt2 predictions indicated that the fecal bacterial function was significantly enriched in the pathway of antibiotic biosynthesis in all three groups. Metabolic pathways related to cell motility (bacterial chemotaxis and flagellar assembly) were significantly more abundant in raptors, while waders were enriched in lipid metabolism (synthesis and degradation of ketone bodies and fatty acid biosynthesis). The fecal microbiota in waterfowl harbored more abundant vitamin B6 metabolism, RNA polymerase and tyrosine and tryptophan biosynthesis. This comparative study revealed the microbial community structure, microbial co-occurrence patterns and potential function, providing a better understanding on the field of ecology and conservation of wild birds. Future studies may focus on unraveling the metagenome functions and the dynamics along with the migration routine or different seasons by metagenomics or metatranscriptomics.